The Timing of Instruction Time: Accumulated Hours, Timing and Pupil Achievement - Paul Bingley; Eskil Heinesen; Karl Fritjof Krassel; Nicolai Kristensen (Institute of Labor Economics (IZA), 2018)
Instruction time varies among schools, subjects, pupils and grades. This variation is positively associated with test scores and has been used to identify modest positive causal effects for instruction hours in certain grades. We exploit administrative data on delivered and timetabled instruction time in each grade throughout compulsory school for three full cohorts of Danish children, and find positive marginal hours effects on 9th grade test scores using accumulated time which are twice as large as when using 9th grade time only. Effects are largest for low SES households and for boys with non-western immigrant background, especially in the early grades.
Keywords: C21; I2; I21; 330; school resources; test scores; time in education